(untitled) (Research, Society and Development, 2021)
The nature and the amount of secondary compounds produced by plant species depends on environmental factors, which can act directly on the synthesis of the secondary metabolites. Hydrocotyle umbellata L. var. bonariensis (Lam.) Mr. Spreng has been traditionally used for medicinal purposes, including for antinociceptive, anti-inflammatory and anxiolytic-like effects, and phytochemical studies revealed its bioactive compounds. This work aimed to evaluate the effects of chemical and organic fertilization, and the soil base saturation correction in the H. umbellata crop in dystrophic yellow latosol soil in the production of the secondary metabolites (total phenolic, total flavonoid and hibalactone). The plant was cultivated in the soil of a rural property in the municipality of Anápolis (Goiás state). The experimental design was completely randomized in a controlled environment. The experiment with fertilization had five treatments (control; cattle manure; poultry manure; chemical fertilization; chemical and organic fertilization) and the experiment with liming included the correction of soil base saturation to 20%, 40%, 60% and 80%. The results in most of the two experiments were not statistically significant in the content of the metabolites studied. In the fertilization experiment, the control and manure treatments were statistically better in the content of total phenols in aerial mass analysis. Regarding the saturation correction experiment, the treatment without liming afforded higher levels of hibalactone content (considering the whole plant) and total phenolic content (considering the air mass). The treatment with correction of saturation to 40% afforded higher levels of total phenolic (considering the whole plant).